2014
DOI: 10.1021/jm5011176
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Mutants of the Interface Residues of Human Thymidylate Synthase Decode Key Features of the Binding Mode of Allosteric Anticancer Peptides

Abstract: Allosteric peptide inhibitors of thymidylate synthase (hTS) bind to the dimer interface and stabilize the inactive form of the protein. Four interface residues were mutated to alanine, and interaction studies were employed to decode the key role of these residues in the peptide molecular recognition. This led to the identification of three crucial interface residues F59, L198, and Y202 that impart activity to the peptide inhibitors and suggest the binding area for further inhibitor design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…In a previous study, we identified seven peptides designed from the dimer interface that inhibit the catalytic activity of the protein by binding at the monomer–monomer interface of the di-inactive form of the protein. 2 The interaction of these peptides with four dimer interface mutants, K47A, F59A, L198A, and Y202A, was explored by Tochowicz et al 28 The results of the present hot-spot structural and functional analysis are here analyzed in combination with those of the above peptide inhibitor studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In a previous study, we identified seven peptides designed from the dimer interface that inhibit the catalytic activity of the protein by binding at the monomer–monomer interface of the di-inactive form of the protein. 2 The interaction of these peptides with four dimer interface mutants, K47A, F59A, L198A, and Y202A, was explored by Tochowicz et al 28 The results of the present hot-spot structural and functional analysis are here analyzed in combination with those of the above peptide inhibitor studies.…”
Section: Discussionmentioning
confidence: 98%
“…Consistently, the interfacial peptides showed the same inhibitory effect against the K47A mutant as against WT hTS. 28 Moreover, the K47E mutant has previously been shown to be active and not resistant to drugs. 40 On the other hand, the double mutant K47Q/D48E exhibits a high level of resistance to 5-FdUR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative approaches may target the same enzymes, without the complications of pool effects and secondary targets. As an example, Cannaza et al 136 have used the crystal structure of human thymidylate synthase to design peptides that inhibit the essential dimerization of the protein, and the same laboratory is working on non-peptide analogues that bind to the same target but that resist degradation and can be taken up into tumour cells 137 . A related approach 138 involves the identification of amino acid residues that are essential to dimerization, leading to the design of dimerization inhibitors that target these sites.…”
Section: Discussionmentioning
confidence: 99%